Kinetic Modeling for the Gas-Phase Hydrogenation of the LOHC γ-Butyrolactone–1,4-Butanediol on a Copper-Zinc Catalyst - Vincent Gautier; Isabelle Champon; Alban Chappaz; Isabelle Pitault (Reactions, 2022)
Liquid organic hydrogen carriers (LOHCs) are an interesting alternative for hydrogen storage as the method is based on the reversibility of hydrogenation and dehydrogenation reactions to produce liquid and safe components at room temperature. As hydrogen storage involves a large amount of hydrogen and pure compounds, the design of a three-phase reactor requires the study of gas and liquid-phase kinetics. The gas-phase hydrogenation kinetics of LOHC γ-butyrolactone/1,4-butanediol on a copper-zinc catalyst are investigated here. The experiments were performed with data, taken from the literature, in the temperature and pressure ranges 200–240 °C and 25–35 bar, respectively, for a H2/γ-butyrolactone molar ratio at the reactor inlet of about 90. The best kinetic law takes into account the thermodynamic chemical equilibrium, is based on the associative hydrogen adsorption and is able to simulate temperature and pressure effects. For this model, the confidence intervals are at most 28% for the pre-exponential factors and 4% for the activation energies. Finally, this model will be included in a larger reactor model in order to evaluate the selectivity of the reactions, which may differ depending on whether the reaction takes place in the liquid or gas phase.